Entre Davi e Golias: consumidores idosos, instituições financeiras e uma avaliação do papel do programa estadual de proteção e defesa do consumidor do estado do Ceará (DECON-CE) no contexto de dominância financeira - Soares, Maísa Martins de Melo (2023)
The study seeks to evaluate the State Program for the Protection and Defense of Consumer in the State of Ceará from the perspective of In-Depth Evaluation. It adopts the triangulation of methods as a research strategy, in a quantitative and qualitative approach. It employs the documental analysis of the reports obtained by the SINDEC system and the registered complaints in DECON-CE, with special attention to the terms of hearing, as a data collection strategy. Prioritizes the quasi-experimental model, using the technique of drawing of time series for the quantitative approach. It also uses the hermeneutic-dialectic model, using Discourse Analysis, according to the perspective of interpretive repertoires, for the qualitative approach. It seeks to understand the multifaceted nature of the phenomenon of consumption from the work of Mike Featherstone and other authors. It seeks to trace a historical path for the consumer market in Brazil, from the interaction between Tupis-Guaranis and foreigners to the current over-indebtedness. It develops the notion of consumer vulnerability and their need of protection, leading to the notion of hypervulnerability. Furthermore, it seeks to trace a historical path of capitalism from primitive accumulation to financial dominance. It investigates the relationship between elderly consumers and financial institutions in the current context. Analyzes the DECON-CE based on the four axes proposed by Lea Rodrigues.